Establishing and developing a Teenage and Young Adult dermatology clinic with embedded specialist psychological support. (18th March 2019) - De Vere Hunt, I.; Chapman, K.; Wali, G.; Bullus, S.; Fisher, R.; Matin, R. N.; McPherson, T.
Summary: Skin conditions are common in adolescence and impart considerable psychological burden. The Department of Health has identified the specialized needs of adolescents transitioning from paediatric to adult services as a priority, yet there are few dedicated transitional clinics in the UK providing appropriate psychosocial support. We have established a monthly Teenage and Young Adult (TYA) dermatology clinic dedicated to managing teenagers and young adults with skin disease alongside open‐access psychological support. Demographic data and Teenagers' Quality of Life Index (T‐QoL) measures were recorded for all patients in 2016. To evaluate patient experience, two online surveys were conducted. Statistically significant improvements in the T‐QoL were recorded for patients with the most common skin condition (eczema) attending for repeat assessment by the psychologist. Patients reported high satisfaction rates in both patient experience surveys. These results demonstrate that specialized adolescent care both is well received and can improve outcomes for these patients.